A decade long experience of anti-neutrophil cytoplasmic antibody testing in a tertiary care referral center in North India: Perspective from a developing country - Ranjana W Minz; Seema Chhabra; Lekha Rani; Surjit Singh; Surinder K Jindal; Vinay Sakhuja (Indian Journal of Pathology and Microbiology, 2011)
Background: In a developing, tropical country like India, discontinuous power supply, high temperatures during summer, and lack of consistent cold chain and funds provide a challenging atmosphere for anti-neutrophil cytoplasmic antibody (ANCA) testing and reporting. However, a simple in-house test and testing algorithm are described here, which have been developed and tested over time. Materials and Methods: An analysis of a decade of testing and reporting of ANCA in the Department of Immunopathology in a tertiary referral health care center was performed to highlight the importance of testing for ANCA in proposed 1999 guideline recommended indications. Results: A total of 4195 ANCA tests were conducted from 2000 to 2009. Overall, 2060 (49%) requests had indications which met the 1999 guidelines, while the remaining 2135 (51%) fell outside the guidelines. A total of 350 samples (8.3%) were positive for ANCA on indirect immunofluorescence (IIF), out of which 212 were guideline recommended and 138 (3.2%) were non-guideline recommended ANCA requests; thus, 3.2% of non-small vessel ANCA associated vasculitis (non-SVAAV) conditions showed false positive results when the population was otherwise unselected. Maximum requests (1432) were for rapidly progressive renal failure/acute renal failure. Conclusions: The audit shows that compliance with guidelines for ANCA testing would decrease the number of false positive results. In-house screening for ANCA by IIF is cost-effective and must be performed at least twice on two different samples from the same patient or on two different sets of ANCA preparations in all the cases who requested ANCA testing with a proposed 1999 guideline recommended indication.